The travels of the prophet ibrahim: quran stories for little hearts - Khan, Saniyasnain; Anand, Achla Anand, Achal K. (Goodword Books New Delhi, 2001)
"The Travels of the Prophet Ibrahim: Quran Stories for Little Hearts" is a delightful children's book that recounts the adventures of Prophet Ibrahim (Abraham) as he journeys in search of truth and understanding of Allah. The story highlights key moments in Ibrahim's life, including his unwavering faith, his challenge against idol worship, and his encounters with various peoples and places. Through engaging illustrations and simple language, the book teaches young readers about the importance of faith, patience, and the quest for knowledge. It aims to inspire children to reflect on their beliefs while introducing them to the profound lessons found in the life of one of Islam's greatest prophets.